Peningkatan Sikap Positif Terhadap Positive Relations With Others Menggunakan Bimbingan Kelompok Teknik Role Playing - Diah Marantika; Shinta Mayasari; Moch Johan Pratama (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
The problem of this research is the students who have negative attitude in positive relations with others at school. The purpose of the research is to increase a positive attitude towards psychological well-being especially the dimensions of positive relations with others. The method used in this study is quasi eksperimen design untreated control group design with dependent pretest and posttest. The research subject used an experimental group of 10 people and a control group of 10 people. Data collection techniques use a scale of positive relations with others. The results showed that positive attitude towards students positive relations with others in schools could be improved through role playing techniques group guidance service, this was shown by the Mean Whitney test results. The results of statistical analysis showed value (Sig.) 0,000 0,05 the Ho was rejected by Ha accepted, meaning that there was an increase in the attitude of students towards positive relations with others after being given group guidance services to role playing techniques in the experimental group. The conclusion is that the positive attitude of students towards positive relations with others can be increased using role playing technique group guidance services in the experimental group at SMA Negeri 7 Bandar Lampung Academic Year 2017/2018.Masalah penelitian ini adalah siswa yang memiliki sikap negatif terhadap positive relations with others. Tujuan penelitian untuk meningkatkan sikap positif terhadap kesejahtraan psikologis khususnya dimensi positive relations with others. Metode yang digunakan dalam penelitan ini adalah quasi eksperimen dengan desain untreated control group design with dependen pretest and posttest. Subjek penelitian ini sebanyak 10 orang kelompok eksperimen dan 10 orang kelompok kontrol. Teknik pengumpulan data menggunakan skala sikap positive relations with others. Hasil penelitian menunjukkan bahwa sikap terhadap positive relations with others dapat ditingkatkan melalui layanan bimbingan kelompok teknik role playing, hal ini ditunjukkan hasil uji Mean Whitney. Hasil analisis statistik menunjukkan nilai (Sig.) 0,000 0,05, maka Ho ditolak Ha diterima, artinya bahwa terdapat peningkatan sikap terhadap positive relations with others setelah diberikan layanan bimbingan kelompok teknik role playing pada kelompok eksp erimen. Kesimpulannya adalah sikap positif terhadap positive relations with others dapat ditingkatkan menggunakan layanan bimbingan kelompok teknik role playing pada kelompok eksperimen di SMA Negeri 7 Bandar Lampung Tahun Ajaran 2017/2018.Kata kunci: bimbingan dan konseling, teknik role playing, positive relations with others